2009
DOI: 10.1007/s11665-009-9572-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fly Ash Particles on the Compressive Properties of Closed-Cell Aluminum Foams

Abstract: The closed-cell aluminum foam reinforced by 1.5 and 3.0 wt.% fly ash particles were manufactured by molten body transitional foaming process. The backscattered electron image shows that fly ash particles distribute uniformly in the cell wall. The quasi-static compression tests were conducted. Results show that Al/Fly ash foams have stable compressive property and the sudden stress drop was not observed. The plateau stress increases nearly linearly with relative density. Moreover, the addition of fly ash partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The MMCs with fly ash addition show a significant improvement in physical and mechanical properties. Applications of fly ash as conventional ceramic particles for foam stabilizing in Al foams are also reported [6]. Fly ash can be sorted into precipitator (solid) and cenosphere (hollow sphere) particles.…”
Section: Introductionmentioning
confidence: 98%
“…The MMCs with fly ash addition show a significant improvement in physical and mechanical properties. Applications of fly ash as conventional ceramic particles for foam stabilizing in Al foams are also reported [6]. Fly ash can be sorted into precipitator (solid) and cenosphere (hollow sphere) particles.…”
Section: Introductionmentioning
confidence: 98%
“…The bulk material porosity and mechanical properties of these structures strongly depend on the filler material. The most common metal matrix material studied is aluminium and its alloys with various filler materials such as silicon carbide (SiC) spheres [1], fly ash cenosphere [9,10] and alumina (Al 2 O 3 ) particles [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another MSF material is developed by Luong et al using aluminium alloy A356 filled with silicon carbide hollow spheres (SiC) [1]. They reported that the compressive and plateau strengths were higher compared to aluminium/fly ash cenosphere metallic syntactic foam under uni-axial loading [9,10,13]. The compressive strengths of Al/SiC foams was recorded at 160 MPa, however for the Al/fly ash cenosphere this parameter was found to be only 75 MPa [10].…”
Section: Introductionmentioning
confidence: 99%
“…The particles can retard drainage by increasing the viscosity of Al melt and prevent cell coalescence by strengthening the cell wall through particle attachment to the gas/liquid interface [5]. The uses of waste products, such as fly ash, instead of expensive ceramic particles, to increase foam stabilisation in Al foams have been reported [6]. Power plant ashes are a by-product waste obtained from thermoelectric power plants which are commonly found to be used in many applications, such as concretes, composite products and landfill facilities.…”
Section: Introductionmentioning
confidence: 99%